Mindful inclusion: strategies for holistic wellbeing in schools - Calcutt, Jane (Frontiers in Education, 2025)
Mental health remains a pressing and persistent concern within educational discourse, influencing the decisions of policymakers, practitioners, and school communities alike. A growing number of children and young people are presenting with symptoms of anxiety, depression, and behavioral difficulties within school settings. Despite the implementation of various wellbeing initiatives, access to appropriate mental health support services across England remains inconsistent and often inadequate. As a result, teachers are frequently left to manage complex mental health needs without sufficient training or resources. While interventions such as mindfulness programmes aim to foster mental wellbeing, they are not always rigorously evaluated or effectively integrated into broader approaches that consider the holistic relationship between body and mind. This paper investigates the multifaceted and interconnected nature of wellbeing, with a particular focus on the dynamic interplay between physical and mental health. It further explores the role of mindfulness practices in educational contexts, considering how such initiatives might extend their impact beyond emotional regulation and metacognitive development. The analysis aims to identify opportunities for developing holistic, inclusive, and sustainable strategies that empower young learners to make healthier, more informed life choices. Ultimately, this paper poses critical questions about prevailing research priorities and the methodological approaches used to define and assess the effectiveness of school-based interventions designed to support and enhance children's wellbeing.